Does the level of burnout differ between occupational groups in Lithuania? - Kalinienė, Gintarė; Ustinavičienė, Rūta; Lukšienė, Dalia; Žutautienė, Rasa; Kirvaitienė, Jolita; Vaičiulis, Vidmantas (Frontiers in Public Health, 2024)
Background The strain on workers of the healthcare system and education sector increased psychological distress and burnout. This study aimed to distinguish the occupational group that is the most affected by occupational burnout and to reveal the scope of psychosocial risk factors among each occupational group. Methods This is a cross-sectional study that analyzed burnout syndrome among 1,046 participants of different occupational groups in association with psychosocial work environment factors in Lithuania. The anonymous questionnaire was composed of the standardized Job Content Questionnaire (JCQ), and the Copenhagen Burnout Inventory (CBI). To find out associations between psychosocial work environment factors and burnout dimensions, a multiple logistic regression model using the stepwise method was applied. Results The burnout levels in all three dimensions (personal, work-related, and client-related burnout) were significantly higher in physicians’ and nurses’ groups compared with public health professionals, teachers, and managers (p < 0.05). The job demands were associated with the personal burnout subscale for all occupations, except public health specialists - each one-unit increase of this variable significantly increased the probability of personal burnout from 10 to 16%, respectively by the occupation. Co-worker support was found to have a buffering effect for all occupational groups, except managers - and significantly reduced personal burnout for physicians (OR = 0.80), nurses (OR = 0.75), public health specialists (OR = 0.75), and teachers (OR = 0.79). Conclusion The burnout levels in all three dimensions differed between occupational groups: there were significantly higher in physicians’ and nurses’ groups compared with public health professionals, teachers, and managers. Considering the occupational preventive measures in the healthcare sector attention should be paid to the reduction of workload and ensuring good relations between co-workers.